EFEKTIVITAS BEBERAPA CARA PENULARAN VIRUS MOSAIK PADA TANAMAN CABAI - Sopialena . (Universitas 17 Agustus 1945 Samarinda, 2014)
The effectiveness of some modes of mosaic virus transmission in chili plants. This study aims to determine the persistence of the mosaic virus in chili and techniques as well as effective mosaic virus infection on chili plants. The experiment was conducted for about four months from land preparation up to the last data collection. Research conducted at the Green House Agronomy Faculty of Agriculture, University Mulawarman. Research and laboratory tests carried out on 35 samples of chili fruit crops, which consists of 25 pieces of diseased plant samples and 10 samples of healthy plants. The results showed that the cause of the mosaic disease in pepper caused by viruses, which dibuktikakan with some testing include: watering with tetracycline antibiotics for 10 days on diseased plants did not show symptoms of healing. Grafting (grafting) between healthy and diseased plants plants rnenunjukkan healthy plant mosaic experience symptoms at week 4 (the virus moves through the vascular tissue). Vector Myzus persicae were introduced into healthy plants for 7 days successfully transmit the virus to healthy plants that exhibit the same symptoms on day ll. Mechanical transmission is not successfully transmit the virus to healthy plants until day 4 after inoculation. The most effective method of infection is by using subsequent grafting by using insects. Meanwhile mosaic virus transmission by mechanical means is not effective because there are no infected plants after mechanically inoculated.